The relationship between inspiratory muscle strength and cycling performance: Insights from hypoxia and inspiratory muscle warm-up - Oliveira, A. L. M. B.; Rodrigues, G. D.; Rohan, P. d. A.; Gonçalves, T. R.; da Silva Soares, P. P. (Journal of Functional Morphology and Kinesiology, 2020)
Hypoxia increases inspiratory muscle work and consequently contributes to a reduction in exercise performance. We evaluate the effects of inspiratory muscle warm-up (IMW) on a 10 km cycling time trial in normoxia (NOR) and hypoxia (HYP). Eight cyclists performed four time trial sessions, two in HYP (FiO2: 0.145) and two in NOR (FiO2: 0.209), of which one was with IMW (set at 40% of maximal inspiratory pressure—MIP) and the other was with the placebo effect (PLA: set at 15% MIP). Time trials were unchanged by IMW (NORIMW: 893.8 ± 31.5 vs. NORPLA: 925.5 ± 51.0 s; HYPIMW: 976.8 ± 34.2 vs. HYPPLA: 1008.3 ± 56.0 s; p > 0.05), while ventilation was higher in HYPIMW (107.7 ± 18.3) than HYPPLA (100.1 ± 18.9 L.min-1; p = 0.05), and SpO2 was lower (HYPIMW: 73 ± 6 vs. HYPPLA: 76 ± 6%; p = 0.05). A post-exercise-induced reduction in inspiratory strength was correlated with exercise elapsed time during IMW sessions (HYPIMW: r = -0.79; p = 0.05; NORIMW: r = -0.70; p = 0.05). IMW did not improve the 10 km time trial performance under normoxia and hypoxia.